Initial Aims as Seeds of Contemplation: A Whiteheadian Interpretation of Merton - Doud, Robert Eugene (Horizons, 1991)
Momentary divine instigations or seeds of love, liberty, and self-realization are showered down upon us inviting us to contemplation, conversion, and commitment. Contemplation knows God as the source of these instigations, and also knows them as a flow of opportunities by which we may respond to God in love. Merton calls these instigations "missions," or "seeds of contemplation." They are identical to Whitehead's "initial aims." Whitehead's distinction of the "initial aim" and the "subjective aim" is important: each moment of emergent human existence is constituted by the tension of these two aims. The "initial aim" is taken in by the newly forming subject and redirected somewhat; that is, the new actual entity modifies the freedom it receives with the freedom of its own subjective decision. The new project designed by the actual entity out of the "initial aim" is called the "subjective aim." The initial aim is the spark of givenness from God by which the new entity originates, and the subjective aim is the appropriation and redirection of this energy on the part of the new actual entity. The reality of contemplation involves attention to the initial aims, while conversion is concerned with the process by which the initial aim becomes the subjective aim.